MAIN DIRECTIONS OF DEVELOPMENT OF SOCIAL ADVERTISING (Web of Teachers: Inderscience Research, 2025)
In world practice, the production and distribution of social advertisements is carried out free of charge, in charitable ways, and only a certain part is financed by the state. Most of the social issues raised in social advertisements have a history of almost half a century, including drug addiction, alcoholism, children's problems, the need for the poor to get higher education, pension issues, the fight against forest fires caused by careless handling of fire, nationwide population registration, violence against children in some families and other social problems.